2008
DOI: 10.4049/jimmunol.180.2.1239
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Cell-Derived Sphingosine-1-Phosphate Promotes HuR-Dependent Cyclooxygenase-2 mRNA Stabilization and Protein Expression

Abstract: Removal of apoptotic cells by phagocytes is considered a pivotal immune regulatory process. Although considerable knowledge has been obtained on the postphagocytic macrophage phenotype, there is little information on molecular mechanisms, which provoke macrophage polarization. In this study, we show that human apoptotic Jurkat cells (AC) or AC-conditioned medium (CM) rapidly induces cyclooxygenase-2 (COX-2) expression in mouse RAW264.7 macrophages via sphingosine-1-phosphate (S1P). Pharmacological inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 47 publications
2
31
1
Order By: Relevance
“…Although S1P is known to directly pass through a plasma membrane and may act as an intracellular second messenger with direct targets that are as yet unknown (2,39), our finding that upregulation of COX-2 by S1P was completely blocked by PTX that inactivates Gi protein indicates that S1P-induced COX-2 expression is mediated through S1P receptors in mouse SEMFs. Although we observed PGE 2 release from SEMFs by S1P treatment, the very recent report using RAW264.7 mouse macrophage-like cell line demonstrates that S1P induced COX-2 expression but not PGE 2 production, because of the lack of phospholipase A2 activation (18).…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although S1P is known to directly pass through a plasma membrane and may act as an intracellular second messenger with direct targets that are as yet unknown (2,39), our finding that upregulation of COX-2 by S1P was completely blocked by PTX that inactivates Gi protein indicates that S1P-induced COX-2 expression is mediated through S1P receptors in mouse SEMFs. Although we observed PGE 2 release from SEMFs by S1P treatment, the very recent report using RAW264.7 mouse macrophage-like cell line demonstrates that S1P induced COX-2 expression but not PGE 2 production, because of the lack of phospholipase A2 activation (18).…”
Section: Discussioncontrasting
confidence: 87%
“…It is recently reported that HETES enhance IL-1-mediated COX-2 expression via p38 and HuR-dependent augmentation of mRNA stability in 18Co human SEMF cell line (11). Moreover, S1P promotes HuR-dependent COX-2 mRNA stabilization in RAW264.7 mouse macrophage-like cell line (18). Therefore we expect that, in mouse SEMFs, S1P induced activation of p38 and PKC leads to COX-2 mRNA stabilization by HuR-dependent mechanism.…”
Section: Discussionmentioning
confidence: 83%
“…We have shown previously that cyclooxygenase-2 is up-regulated under hypoxia in a HIF-1-independent fashion (5). It is interesting to note that S1P is a potent inducer of cyclooxygenase-2 expression (22,47), thus opening the possibility that S1P is responsible for cyclooxygenase-2 induction and the formation of antiapoptotic prostaglandin E 2 under hypoxia. This might help to understand how signaling pathways cooperate in cell protection within hypoxic tumor regions.…”
Section: Cm(hypoxia)mentioning
confidence: 99%
“…It is thought that COX-2 inhibitors prevent the development of resistance to different cytostatics and that COX-2 overexpression induces increased multidrug resistance protein 1 (MRP1) expression in different cancer cells [99][100][101][102] . Schnitzer et al showed that COX-2 is upregulated under hypoxia in a HIF-1-independent fashion and sphingosine-1-phosphate (S1P) is responsible for COX-2 induction under hypoxia in A549 lung cancer cells 103 . Simultaneous inhibition of HIF-1 and COX-2 strongly suppresses chemoresistance and the inhibition of only COX-2 decreases chemoresistance of cancer cells in hypoxia 33 .…”
mentioning
confidence: 99%